2021
DOI: 10.1186/s12888-021-03372-2
|View full text |Cite
|
Sign up to set email alerts
|

Now and then: a ten-year comparison of young people in residential substance use disorder treatment receiving group dialectical behaviour therapy

Abstract: Background Reducing substance use in youth is a global health priority. We compared two cohorts from the same 12-week residential substance use disorder (SUD) facility over a 10 year period: Cohort A (2008–2009) and Cohort B (2018–2020). The essential components of the program remained the same with the primary treatment being dialectical behaviour therapy (DBT) plus residential milieu. Methods Young people in the current Cohort B (N = 100) versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…The findings are consistent with research demonstrating that when treatment concurrently addresses psychiatric and substance use disorders, improvements in both domains can be achieved (Azrin et al, 2001;Bergman et al, 2014;Esposito-Smythers et al, 2011;Godley et al, 2014;Hides et al, 2010;Hogue & Liddle, 2009;Marceau et al, 2021;Rohde et al, 2014;Ryan et al, 2013). These findings extend this research to inpatient settings, suggesting the delivery of evidence-informed integrated treatment in an inpatient setting for adolescents can be effective.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The findings are consistent with research demonstrating that when treatment concurrently addresses psychiatric and substance use disorders, improvements in both domains can be achieved (Azrin et al, 2001;Bergman et al, 2014;Esposito-Smythers et al, 2011;Godley et al, 2014;Hides et al, 2010;Hogue & Liddle, 2009;Marceau et al, 2021;Rohde et al, 2014;Ryan et al, 2013). These findings extend this research to inpatient settings, suggesting the delivery of evidence-informed integrated treatment in an inpatient setting for adolescents can be effective.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, substantial attrition over the follow‐up period may have impacted the validity of the results. High attrition rates are a common problem in substance use treatment research, particularly involving youth (Farabee et al, 2011; Marceau et al, 2021). The study's results indicated no significant differences at admission between those who did and did not participate during the post‐discharge period; however, the severity of psychiatric conditions has been associated with difficulty contacting adolescent participants in longitudinal research (Allott et al, 2006), and attrition may reflect instability in important aspects of functioning (e.g., living situation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 15 articles were included in the systematic review. Characteristics of the Literature Among the 15 eligible articles for the systematic review, 14 studies were published after 2004, demonstrating recent valid results [30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Five articles were from Australia four articles from Europe and six articles from Asia [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Literature Search Resultsmentioning
confidence: 98%
“…As adolescence and young adulthood are vulnerable age stages for the development of mental disorders, early identification and tailored intervention planning should be an integral part of a placement and admission process in which the resources and strengths of these adolescents should be adequately assessed [73]-especially by offering continuity in evidence-based psychotherapy and well-prepared transitions [15,[74][75][76]. For example, primary treatment modalities (e.g., family-based therapies and multicomponent interventions) have been suggested as primary strategies for treating substance-use disorders among adolescents, and a dialectical-behavioral therapy plus milieu approach demonstrated sustained positive treatment outcomes [77,78]. Furthermore, evidence-based practices have been shown to be relevant to group care and residential treatment settings for children in the child welfare system [74].…”
Section: Limitations and Implicationsmentioning
confidence: 99%